The Effects of Chemistry Virtual Laboratories in Academic Achievement of Secondary Level Learners: A Meta-Analysis - Richelle Castro (Integrated Science Education Journal, 2025)
Purpose of the study: Chemistry education is continuously improving to provide appropriate learning for the students. The dynamic shaping of technology in the education induces innovative strategies including the utilization of virtual laboratories. This study explores the topic of examining the effectiveness of virtual laboratories in improving learner’s academic achievement in secondary level chemistry. Methodology: To facilitate the meta-analysis, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol was used. Only 17 studies that met the inclusion criteria were included in the study. Using the Review Manager Version (RevMan) 5.4 software, the standardized mean difference (SMD) was used to measure the effect of virtual laboratory in enhancing learners’ achievement. Main Findings: The meta-analysis discovered the effect size of SMD = 0.98 which can be interpreted as positively large effect size of virtual laboratories in the academic achievement. Sub-groping was also utilized in this study due to the heterogeneous collected data which revealed the effect sizes according to the region, grade level, topic in chemistry, and duration of implementation. Novelty/Originality of this study: This study aims to synthesize current studies on the use of virtual laboratories in chemistry that focus on secondary-level students. This meta-analysis provides a comprehensive overview for the teachers, researchers, and policy-makers as a basis for the effectiveness of virtual laboratory integration in education. This may help the chemistry instructors design appropriate strategies for utilizing virtual simulations.